PREVENTION OF CORRUPTION AS ADMINISTRATIVE ACTIVITY OF AUTHORITIES AND THE OBJECT OF PROSECUTOR’S OBSERVANCE - T. L. Kozlov (Russian Journal of Economics and Law)
Objective: to study corruption prevention as administrative activity of state and municipal authorities.Methods: dialectical, systematic, formal-legal analysis, synthesis, statistical and specific sociological methods.Results: basing on the study of counter-corruption legislation, its implementation, and acts of prosecutorial response, the definition of the concept "corruption prevention" was formulated, which refers to administrative activities of state and municipal bodies and their officials aimed at the implementation of legislation on combating corruption. The feature of the preventive component of counter-corruption legislation is that it brings together the complex of binding, prohibitive and restrictive rules established for the prevention of corruption. Corruption prevention is implemented through a specific type of managerial (administrative) activity. The legality of this activity is provided by means of prosecutorial supervision over implementation of laws on corruption prevention.Scientific novelty: for the first time in the article corruption prevention is viewed not as a criminological category but as an institution of administrative law, characterized by the essential features of the state (municipal) control.Practical significance: the main provisions and conclusions of the article can be used in research and law-enforcement activities in addressing issues related to combating corruption.